1973
DOI: 10.1099/00222615-6-4-527
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Histamine Sensitisation Produced in Mice by Corynebacterium Parvum

Abstract: IT has been known for many years that mice treated with Bordetella pertussis vaccine not only become resistant to challenge with the living organisms but are also sensitised to pharmacological agents and to various stressing treatments. A single injection of suitably grown and killed Bord. pertussis organisms or of " histamine-sensitising factor " extracted from them produces sensitisation to histamine, serotonin, bradykinin, endotoxin, cold shock, X-rays and anaphylaxis. Recent studies suggest that these seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1975
1975
1982
1982

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Since Halpern et al [21] reported that Corynebacterium parvum stimulated the carbonclearing activity in mice, it has been known that anaerobic coryneforms including C. parvum, Corynebacterium acnes and Corynebacterium granulosum showed several biological activities, such as antitumor action [10,13,16,18,20,26,35], adjuvant action in immune response [23,29,33,34,38,40], resistance to bacterial infection [2,11,19] and enhancement of histamine sensitivity in animals [1]. Anaerobic coryneforms inhabit the skin, oral cavities, intestines or vaginas of humans, and some of them may be isolated from comedones, pustules and acne vulgaris lesions.…”
mentioning
confidence: 99%
“…Since Halpern et al [21] reported that Corynebacterium parvum stimulated the carbonclearing activity in mice, it has been known that anaerobic coryneforms including C. parvum, Corynebacterium acnes and Corynebacterium granulosum showed several biological activities, such as antitumor action [10,13,16,18,20,26,35], adjuvant action in immune response [23,29,33,34,38,40], resistance to bacterial infection [2,11,19] and enhancement of histamine sensitivity in animals [1]. Anaerobic coryneforms inhabit the skin, oral cavities, intestines or vaginas of humans, and some of them may be isolated from comedones, pustules and acne vulgaris lesions.…”
mentioning
confidence: 99%
“…Out of a wide series of bacterial cells, including B. pertussis and H. influenzue, only B. pertussis had histamine sensitizing properties in mice (Munoz & Bergman, 1968). However the specificity of B. pertussis in this respect can be doubted: Corynebucferium p m u m has been shown to have histamine sensitizing effects on several mouse strains (Adlam, 1973). Most of the bacteria investigated, except H. influenzue, belong to familiae or ordines taxonomically different from the one to which B. pertussis belongs, that is Eubacteriales, Brucellaceae.…”
Section: Discussionmentioning
confidence: 98%
“…However, only a few papers deal with the specificity of the model: in these cases histidine decarboxylase activity and the sensitivities to histamine, methacholine and serotonin were used as parameters (Anand, Itkin & Kind, 1968;Schayer & Ganley, 1961;Munoz & Bergman, 1968; Adlam, 1973). Out of a wide series of bacterial cells, including B. pertussis and H. influenzue, only B. pertussis had histamine sensitizing properties in mice (Munoz & Bergman, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination with B. pertussis resulted in ^-adrenergic blocking effects of adrenaline-induced hy perglycemia, isoprenaline-induced heart rate changes and histamine-induced wheals [18]. Corynebacterium pcirvum also enhanced the sensitivity to histamine in certain rat strains [1]. In the case of B. pertussis, the histami ne-sensitizing effects are ascribed to a his tamine-sensitizing factor (HSF), a lipopro tein fraction isolated from B. pertussis vac cine.…”
Section: Discussionmentioning
confidence: 99%